Answer:
~q→~p
Step-by-step explanation:
The contrapositive of a statement is formed by negating the hypothesis and conclusion of a statement and switching them (the hypothesis becomes the conclusion and vice versa).
With this definition we can conclude that the contrapositive of p→q would be ~q→~p
Answer:
The Answer would be C, i think
Step-by-step explanation:
Answer:
She'll spend 192 because 2400 divided by 48 equals 50 times that by 3.84 which will give you 192.
Gf(x)
=g[f(x)]
=g[x2-1]
=x2-1+2